Efektivitas Metode Pembelajaran Berbasis Masalah (PBM) dalam Meningkatkan Prestasi Siswa di SMAN 1 Monta - Sukarni, Sukarni; Azmin, Nikman; Hartati, Hartati (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2025)
This study aims to analyze the effectiveness of Problem Based Learning (PBM) method in improving students' learning achievement on Mutation material in class XII SMAN 1 Monta. The research method used was quantitative with quasi-experimental design. The research sample consisted of 58 students divided into experimental group (n=29) and control group (n=29) obtained through simple random sampling technique. The data collection instrument was a learning achievement test consisting of 30 multiple choice questions given at the pre-test and post-test. Data analysis was conducted with descriptive statistics and inferential statistics using t-test. The results showed that the average score of students' learning achievement in the experimental group using PBM method was significantly higher than the control group using conventional learning method. This research indicates that the application of PBM method is effective in improving students' learning achievement on Mutation material. Based on these results, the PBM method is recommended to be implemented by teachers in learning Biology at school. Further research on the effectiveness of the PBM method in other subjects and different levels of education needs to be done to enrich the treasure of knowledge in the field of education.